Relationship between underweight or overweight and the physical fitness of girls from Eastern Poland - Popławska, Helena; Dmitruk, Agnieszka; Hołub, Wojciech; Wilczewski, Adam (Polish Journal of Public Health, 2011)
Introduction. The development of motor capabilities in children and adolescents is determined by selected traits and the parameters of their somatic build. Aim. The objective of this study was to determine the structure of physical fitness of underweight or overweight girls compared to subjects with normal BMI levels. Material and methods. The study involved 1421 girls from Eastern Poland. The incidence of underweight, overweight or obesity was evaluated with boundary BMI values for children and adolescents recommended by Cole et al. (2000, 2007). Surveyed girls from particular age categories (10-15 years of age) were classified into the following groups: underweight subjects (Group A), subjects with normal BMI values (Group B), and overweight and obese subjects (Group C). The physical fitness of particular groups was assessed using trials of running endurance, trunk strength, arm strength, flexibility, and total body balance. The results of Group A and Group C subjects were standardized to the arithmetic mean and standard deviation of the results obtained by girls with normal BMI values (Group B). Results. In the surveyed population, the incidence of underweight subjects was higher than the occurrence of overweight or obese subjects (14.9% vs. 8.6%, respectively). Underweight girls achieved the best results in tests assessing running endurance and arm strength. Their remaining motor capabilities were similar to those in girls with normal BMI values. Overweight and obese girls from lower age categories were characterized by the lowest levels of running endurance, total body balance, and arm strength. Conclusions. The results obtained in this study allow us to conclude that children and adolescent girls who are underweight, overweight and obese have different physical fitness levels. Lower levels of physical fitness are often associated with excessive body mass.